2006
DOI: 10.1016/j.jvs.2006.05.013
|View full text |Cite
|
Sign up to set email alerts
|

An intention-to-treat by endovascular repair policy may reduce overall mortality in ruptured abdominal aortic aneurysm

Abstract: Although the number of patients was small, offering EVAR to as many patients as possible with ruptured AAA has resulted in a 20% reduction in mortality, albeit statistically insignificant. However, it is in the unstable patients that EVAR will need to improve survival before it may be hailed to supersede the conventional approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 18 publications
(33 reference statements)
2
32
0
Order By: Relevance
“…This decrease in death relative to our retrospective published data follows the application of an intention-totreat by eEVR protocol and the use of hypotensive hemostasis. 35 Both groups in this study had comparable Hardman scores, mean systolic blood pressure, and comorbidities that should have minimized the selection bias between the groups. Although eEVR resulted in reduced blood loss, blood transfusion, and fluid requirements, its impact on hospital stay was probably masked by the major trauma effect of the rAAA.…”
Section: Discussionmentioning
confidence: 93%
“…This decrease in death relative to our retrospective published data follows the application of an intention-totreat by eEVR protocol and the use of hypotensive hemostasis. 35 Both groups in this study had comparable Hardman scores, mean systolic blood pressure, and comorbidities that should have minimized the selection bias between the groups. Although eEVR resulted in reduced blood loss, blood transfusion, and fluid requirements, its impact on hospital stay was probably masked by the major trauma effect of the rAAA.…”
Section: Discussionmentioning
confidence: 93%
“…Other institutional studies have reported mortality rates of 8% to 40%, but the number of patients within institutional studies, however, is still quite small. [2][3][4][5][6][7][8] Two recent meta-analyses reported pooled outcomes on EVAR for RAAA procedures. Rayt et al 12 found a mortality of 24% for 982 patients, while Azizzadeh et al 13 reported a mortality of 30% in 531 patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 With emerging data from centers of excellence and community hospitals, it is apparent that EVAR for RAAA has shown a steady increase. [2][3][4][5][6][7][8] Comparison of this method of repair to its traditional open repair counterpart is difficult, however, as preoperative differences in hemodynamic stability are likely to play a large role in the decision for one type of repair over the other.…”
Section: ¤ ¤mentioning
confidence: 99%
“…Several studies compare early mortality and morbidity in endovascular repair vs open repair, [13][14][15][16][17][18][19][20][21][22] and most of them show a reduction in early complications and mortality. [13][14][15][16][17][18][19]21 In acute conditions like rAAA, truly randomized studies are difficult to perform. As a result of lack of randomization, comparative studies so far are flawed by methodologic inadequacies such as selection bias, which is created by inadequate control of potential confounding secondary to inadequate patient matching.…”
mentioning
confidence: 99%